2021
DOI: 10.3389/fpsyg.2021.621853
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing the Neurobiology of Resilience to Protect the Mental Well-Being of Healthcare Workers During the COVID-19 Pandemic

Abstract: Healthcare workers are at a high risk of psychological morbidity in the face of the COVID-19 pandemic. However, there is significant variability in the impact of this crisis on individual healthcare workers, which can be best explained through an appreciation of the construct of resilience. Broadly speaking, resilience refers to the ability to successfully adapt to stressful or traumatic events, and thus plays a key role in determining mental health outcomes following exposure to such events. A proper understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 186 publications
(240 reference statements)
0
10
0
Order By: Relevance
“…Moreover, the COVID-19 virus may be affected by host nutritional deficiency; it may be more virulent if it replicates in a nutritionally deficient host [29]. Moreover, there is preliminary evidence that some nutrients may modulate stress resilience in humans [32], which could help in planning healthy meals for HCWs [33].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the COVID-19 virus may be affected by host nutritional deficiency; it may be more virulent if it replicates in a nutritionally deficient host [29]. Moreover, there is preliminary evidence that some nutrients may modulate stress resilience in humans [32], which could help in planning healthy meals for HCWs [33].…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation for the absence of association between cortisol change and PTSD, anxiety, and depression can be that cortisol may not be an important pathophysiological mechanism underlying these disorders. A recent review summarized six possible biological mechanisms responsible for variations in resilience in healthcare workers facing the COVID-19 pandemic ( Rajkumar, 2021a ). In addition to the hypothalamic-pituitary-adrenal axis studied in the present paper, they identified brain neurotransmitters, immune system, neuropeptides, epigenetic and environmental factors as possible mediators.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the hypothalamic-pituitary-adrenal axis studied in the present paper, they identified brain neurotransmitters, immune system, neuropeptides, epigenetic and environmental factors as possible mediators. Another lead would be heart rate variability as it is a known measure of the autonomous nervous system balance ( Rajkumar, 2021b ) and is reduced in anxiety disorders ( Chalmers et al, 2014 ). Finally, while we did not study the downstream effects of changes in cortisol levels on burnout, Onen Sertoz et al did, and their results suggest that the serum brain-derived neurotrophic factor circulating biomarkers may be involved ( Onen Sertoz et al, (2008.…”
Section: Discussionmentioning
confidence: 99%
“…This outcome was observed in our data, which showed that Brazilian physiotherapists who maintained and engaged in physical activity had better perceptions of QoL and happiness. Regular physical exercise may: increase the local expression of the brain-derived neurotrophic factor (BDNF) gene in brain areas involved in resilience, such as the hippocampus and prefrontal cortex; minimize the risk of post-traumatic stress symptoms; increase heart rate variability; and promote neuropeptide secretion [ 98 ].…”
Section: Discussionmentioning
confidence: 99%